Handbook of microalgal culture : applied phycology and biotechnology - Richmond, Amos; Hu, Qiang, 1960- (Chicester, West Sussex : Wiley Blackwell, 2013)
Algae are some of the fastest growing organisms in the world, with up to 90% of their weight made up from carbohydrate, protein and oil. As well as these macromolecules, microalgae are also rich in other high-value compounds, such as vitamins, pigments, and biologically active compounds, All these compounds can be extracted for use by the cosmetics, pharmaceutical, nutraceutical, and food industries, and the algae itself can be used for feeding of livestock, in particular fish, where on-going research is dedicated to increasing the percentage of fish and shellfish feed not derived from fish.
3.4.4 Moisture content and ash content3.4.5 Chlorophyll determination; 3.4.6 Total organic carbon (TOC) measurement; 3.4.7 Doubling time, specific growth rate, and output rate; 3.4.8 Growth yield; 3.4.9 Maintenance energy requirement; 3.5 MODES OF CULTURE; 3.5.1 Batch culture; 3.5.2 Continuous cultures; 3.5.3 Immobilized cultures; 3.6 ADVANCED BIOCHEMICAL ANALYSIS; 3.6.1 Carbohydrates; 3.6.2 Proteins; 3.6.3 Lipids; 3.6.4 Fatty acid composition analysis; 3.6.5 Lipid determination using fluorescence spectroscopy and microscopy; ACKNOWLEDGMENT; REFERENCES.
4 Strategies for Bioprospecting Microalgae for Potential Commercial Applications.
Includes bibliographical references and index.
Print version record.
Keywords: Algae culture; Microalgae -- Biotechnology; Microalgae -- Cultures and culture media; Algae culture -- Handbooks, manuals, etc; Algology -- Handbooks, manuals, etc; Algology; Microalgae -- Biotechnology -- Handbooks, manuals, etc; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Algae culture; Microalgae -- Biotechnology; Microalgae -- Cultures and culture media; Electronic books; Electronic books